Evaluation of a new disposable "tampon like" electrostimulation technology (Pelviva®) for the treatment of urinary incontinence in women: A 12‐week single blind randomized controlled trial1234567. Issue 5 (28th September 2012) - Oldham, Jackie; Herbert, Julia; McBride, Kathryn
Abstract Aims To test the null hypothesis that a novel disposable "tampon like" electrostimulation device (Pelviva®) is no better than unsupervised pelvic floor muscle exercise for treatment of urinary incontinence in women. Methods Pre/post‐intervention assessor blinded, single center RCT. A total of 123 community dwelling self referred women with symptoms of stress, urge, or mixed incontinence were randomly assigned to one of two 12‐week duration treatments: Pelviva® used for 30 min a day plus unsupervised pelvic floor muscle exercise or unsupervised exercises alone. Outcome measures included ICIQ‐UI (primary), ICIQ FLUTSex and global impression of severity and improvement (secondary) completed at recruitment, after 4 weeks of unsupervised exercise and immediately post‐treatment. Diary of exercise frequency/type, overall impression, and usage of device was completed mid‐ and post‐treatment. Results Pelviva® plus exercise produced significantly better outcome than unsupervised exercise alone: 5 points (45%) versus 1 point (10%) for ICIQ‐UI (P = 0.014); 67% versus 33% for leak frequency (P = 0.005); 40% versus 20% for leak interference with life (P = 0.018). Incontinence was less bothersome during sex to a greater extent in the Pelviva® group (P = 0.026). Women were enthusiastic about the device, found it comfortable/easy to use and experienced no adverse events. Conclusions The Pelviva® device plus unsupervised exercise is more successful than unsupervised pelvic floor muscle exercise alone in treating urinary incontinence. The device is easy/comfortable to use, there are no apparent adverse incidents, and women can manage their incontinence in the privacy of their own home. The product will be launched 2013. Neurourol. Urodynam. 32: 460–466, 2013. © 2012 Wiley Periodicals, Inc.